Basic electronics - Grob, Bernard (New York : Glencoe/McGraw-Hill, 1997)
Electricity. Resistors. Ohm's law. Series circuits. Parallel circuits. Series-parallel circuits. Voltage dividers and current dividers. Direct-current meters. Kirchhoff's laws. Network theorems...
Includes bibliographical references and index.
Keywords: Electronics; Electronics